Physical properties of banana pseudo-Stem woven fabric treated with softening agent / Wan Syazehan Ruznan ... [et al.] - Ruznan, Wan Syazehan; Ahmad Suhaimi, Suraya; Mohd Yusof, Nor Juliana; Pairan, Nazzuha; Mazlan, Aimi Umairah; Azrain, Anis Naziihah; Md Rosli, Intan Shahirah; Othman, Nur Izzati (Universiti Teknologi MARA, Negeri Sembilan, 2020)
Fibres from banana's stem are abundantly available in Malaysia. This study focused on the production of woven fabric from banana pseudo-stem fibres. Yarn made of 100% banana stem and 100% cotton yarn were produced. Two types of retting techniques were conducted, which are water retting and retting using softening agent. The fibres were spun and weaved into plain weave fabric. All specimens were evaluated for yarn twist, yarn evenness, yarn linear density and selected fabric physical properties. The results obtained showed that banana stem fabric treated with softening agent has lower area density and higher thickness. Weft sample retted in softening agent has higher bending length and flexural rigidity than sample retted in water. This might be due to the decrement of yarn's stiffness, which eases the insertion of yarn during shedding process. Weft sample retted in water has lower bending length due to coarser yarn and tends to break easily. It is found that retting banana stem fibres with softening agent affect the yarn linear density, area density, fabric stiffness properties and flexural rigidity of the fabric.